Medical negligence and likely developments in Oman. (September 2019) - Farrukh, Affifa; Mayberry, John F
Medical mistakes can never be eliminated but they can be minimised. From the world of aviation, it is clear that simulation training can have dramatic beneficial effects. Such training, however, is compulsory. In contrast, in the world of medicine there are few countries which have adopted a comparable approach. Unless continued medical registration is directly linked to satisfactory performance in simulated exercises and real events, it is unlikely that significant reductions will be achieved. This review will concentrate on the situation where mistakes and their mismanagement have direct and adverse consequences for patients. It will not be concerned with the recognised complications of procedures and treatments, with the exceptions of poor communication where patients have entered into treatments unaware of the associated risks.